Particle Removal and Antibacterial of Nanofiber Doped with Metal and Ions Prepared by Electrospinning - Ying-Chi Jiang; Hope T. Cayron; Yu-Chen Cheng; Alvin R. Caparanga; Chang-Tang Chang (Aerosol and Air Quality Research)
Abstract Due to the increase in human activities and the application of nanotechnology, people’s exposure to nano and submicron particles is increasing. Conventional particle separation technologies, such as electrostatic precipitators, cyclone, wet washing, and filtration method, cannot work well. In addition, the fiber diameter and pore size of the traditional fiber filter material is too large, and the bulk density is difficult to control. Nanofiber membranes have a large surface area, small pore size and high porosity. The nanofiber membranes prepared by electrospinning technology are easy to intercept submicron and nanoparticles. Furthermore, the electrospinning technology is simple to operate, makes fibers of various materials easy, and is convenient for assembly and replacement. The most common bacteria are Escherichia coli, which harms the ecological environment and human health. Therefore, this study used bacteria and particles as the target pollutants and controlled by prepared nanostructured materials doped with metals and ions. In order to improve the treatment efficiency of particles and bacteria, this study added various metals and ions to nylon 6 nanofibers and explored the antibacterial and filterability of artificial fibrils. Different operation parameters, such as types of metal, types of ion, metal and concentration, and surface velocity, were also investigated to prepare various fibers to make the best performance fiber. In addition, the best-operating conditions could be obtained through a filtration test. Different salts, metals and metal ions with different concentrations, three metal oxides (TiO2, CeO2, and ZnO) and three ions (Ag+, K+, and Na+) were used to test the filtration performance of various particle sizes for the best metal ion concentration, best filtration and bacterial removal performance. The experimental results show that the filtration efficiency of the composite fiber can reach 99%, and the composite fiber sprayed with a self-made antibacterial liquid has the best antibacterial ability.